A study of an effect of the parameters of niobium-based ion cleaning of a surface on its structure and properties - Postelnyk, H. O.; Knyazev, S.; Meylekhov, A. A.; Stolbovoy, V. A.; Kovteba, D. V. (PC тесhnology сеntеr, 2017)
The paper describes using techniques of structural engineering in a comprehensive study of the effects of the negative displacement potential, nitrogen and argon pressures, as well as the distance from a sample to the cathode on the processes of sputtering and depositing. In practice, it is highly important to obtain steel surfaces with high mechanical properties and low roughness. The highest microhardness is manifested at the highest degree of sputtering on the samples at Ub=–1,300 V. It has been determined that the presence of nitrogen in the vacuum chamber shifts the equilibrium point of sputtering and depositing towards a higher Ub. It has been established that the presence of argon in the ion bombardment process increases the sputtering rate, whereas the presence of active nitrogen gas reduces the deposition rate due to nitride formations on the surface. The point “sputtering-depositing” shifts: in the case of Ar (from Ub=–350 V to Ub=–200...–300 V) when the RN increases from 0.002 Pa to 0.66 Pa, respectively. In the case of nitrogen, when PN increase from 0.02 Pa to 0.08 Pa, the point shifts from Ub=–400 V to Ub=–600 V (at a distance of 300 mm from the cathode to the sample).
Keywords: plasma; vacuum arc evaporation; displacement potential; microhardness; deposition; mixing; sputtering; substrate